Performance and Nutrient Utilization in Laying Hens Fed Iodine Supplemented Diets - Sumaiya, Shaikh; Nayak, Sunil; Baghel, R.P.S.; Khare, Ankur; Malapure, C.D.; Kumar, Rajesh (Indian Journal of Animal Nutrition, 2018)
A total of 135 layers of 55 weeks age were randomly distributed into 5 dietary treatments with 3 replicates having 9 birds each. Layers of group T1 (Control) were fed basal diet. Diets of layers in group T2, T3, T4 and T5 were same as T1 except that in these diets iodine was supplemented as calcium iodate in such a way that respective diets contained 3.25, 6.50, 9.75 and 13.0 mgI/kg feed. Total experimental period lasted for ten weeks. Weight gain (g/hen), feed intake (g/hen/day), cumulative feed intake (kg/hen) and hen-day egg production (%)was comparable in groups T1, T2 and T3, however, lower (P